Interpersonal relations in the educational and manufacturing organizations - Gocevska, Jasmina; Angeloska Galevska, Natasha (The Association for the Development of Science, Engineering and Education, Serbia, 2015)
Success and efficiency in the working organizations today are based upon good communication and social relations between their employees. The importance of these processes is visible in the use of modern techniques of communicating and the support of team building and team work in organizations. Communication and social climate is a topic that is contemporary and interesting to explore. Therefore, this research is focused on processes of communication and social interaction in the educational and manufacturing working environments. Research data were gathered with survey on a sample of 121 workers from two educational and two manufacturing working organizations. Two types of questionnaires were used: a questionnaire by Richard L. Daft on the communication issue and so-called WES Work Environment Scale concerning social interaction. Data were analysed with statistical procedures of descriptive statistics (frequencies, percentage, mean and standard deviation) and inferential statistics (t-test) for testing of hypotheses. Based upon this analysis came the conclusion that there is a difference in the degree of development of these important personal skills. The results show that the workers in the educational working organizations have a greater ability to communicate and interact compared to those in the manufacturing organizations. This research is meant to be a base for conclusions that came by information gathered in these two kinds of organizations so that the insight could lead further research in other types of organizations.
Keywords: social interaction, communication, working organisations